A rare case of temporal and infratemporal space abscess secondary to masseteric space infection - Narayana, Mada Lakshmi; Gaur, Urvashi; Chaithanya, N. Reddy; Sravani, Addanki Lakshmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Abscess in the temporal and infratemporal space are very rare. They develop as a result of the extraction of infected maxillary molars. Temporal space infections or abscess can be seen in the superficial or deep temporal regions. A 27-year-old lady who had undergone extraction of 2nd mandibular molar five days ago came with complaints of painful swelling over left cheek and restricted mouth opening. On examination, an ill-defined diffuse parotid swelling was seen and treated with empirical antibiotics for which patient didn’t respond. On examination, a diffuse hourglass swelling was seen extending from left parotid region to temporal region. CT scan revealed a bulky parotid gland with abscess involving parotid, masticator, infratemporal and temporal scalp region with reactive cervical lymphadenopathy on the left side. Surgical drainage of the abscess was done from the temporal space; subsequently, all other space abscess resolved. On conclusion, masseteric space infection leads to infratemporal and temporal space abscess as they communicate. Drainage of abscess from temporal space is adequate to resolve the abscess from other masticator spaces.